Early stage network engagement strategies in the network capability development of new ventures. Issue 9 (1st February 2021) - McGrath, Helen; O'Toole, Thomas
Abstract : Purpose: The purpose of this paper is to identify the early stage network engagement strategies that new ventures use to gain traction in interaction in the development of network capability. Design/methodology/approach: Using 24 new ventures in the micro-brewing industry in Ireland, Belgium and the USA as an empirical base, the authors use an inductive case study approach owing to the exploratory nature of the research aim and the lack of prior literature in the area. Findings: The findings suggest five early stage network engagement process strategies in network capability development: business-to-business network prospecting; co-branding/co-promoting activities; from maker-mindset to adapting; social media platforming; and recognition and activation of network role. Research limitations/implications: The findings are limited to the micro-brewery sector at one point in time, although in multiple country contexts. Analyzing other sectors and taking a temporal view of strategizing, analyzing the sector at another time point, would show how dynamics in engagement change as the actors acquire new experiences from interaction. Practical implications: The potential to gain from network resources and the paucity of these resources in new ventures makes early stage engagement strategizing for network capability development an attractive business strategy for new firms. All firms are born within a social network that has economic importance. Identifying the five early stage network engagement strategies can mitigate the challenge for the new venture in moving from the initial social network to collaborating within wider business networks to gain access to resources, technology and customers. Originality/value: Strategizing in new venture contexts is a relatively new stream of research for the industrial marketing and purchasing group. This paper adds to the growing body of literature that places interaction, relationships and networks at the heart of strategy making and provides important insights for new ventures, which may lead to earlier and greater success for the firms. The authors respond to calls for increased research addressing capability development in a new venture context and for research to take a more interactive perspective on new venture processes.